Refined target-mediated drug disposition modeling of the anti-tissue factor pathway inhibitor antibody MG1113 in cynomolgus monkeys and rabbits - Kwak, Heechun; Jeong, Yoo-Seong; Kim, Jiyoung; Lee, Minsoo; Byoun, Seonyoung; Aoki, Yasunori; Chung, Suk-Jae; Lee, Wooin (Frontiers in Pharmacology, 2026)
IntroductionMG1113 is a humanized immunoglobulin G4 antibody targeting the Kunitz-type protease inhibitor 2 domain of tissue factor pathway inhibitor (TFPI) and is under clinical investigation for hemophilia treatment. This study aimed to refine a previously developed target-mediated drug disposition (TMDD) model for MG1113 by incorporating both targets [e.g., soluble TFPI-α (sTFPI-α) and membrane-bound TFPI (mTFPI)] and a transit compartment to capture delayed absorption after subcutaneous (s.c.) dosing.MethodsThe refined TMDD model was fitted to the plasma profiles of MG1113 and sTFPI-α in cynomolgus monkeys that received various intravenous and s.c. doses of MG1113 using the Cluster Gauss-Newton Method (CGNM). The optimized model parameters were scaled allometrically and used to simulate the concentration-time profiles of MG1113 and sTFPI-α in rabbits and humans.ResultsThe refined TMDD model provided an improved model performance overall, compared to the previous model when fitted to monkey data. When extrapolated to rabbits, the model prediction showed a good agreement with the observed MG1113 and sTFPI-α data, supporting its interspecies applicability. In humans, the model prediction suggested that maintaining sTFPI-α suppression below 25% of baseline, a level associated with therapeutic efficacy, could be achieved with a weekly dose of 3.3 mg/kg MG1113.ConclusionThe refined TMDD model better characterized the nonlinear pharmacokinetic and pharmacodynamic profiles of MG1113 across species by incorporating both targets and delayed absorption after s.c. dosing. This model enabled quantitative prediction of sTFPI-α suppression in relation to MG1113 dose and baseline target levels, supporting a rational dose selection for ongoing and future clinical studies.